2018
DOI: 10.4103/jisp.jisp_359_16
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparative evaluation of periodontally accelerated osteogenic orthodontics with piezo and surgical bur: An interdisciplinary approach

Abstract: Context:The orthodontic treatment in adult for the treatment of malocclusion is becoming more common. However, the disadvantages of conventional orthodontics are the time consumed for the treatment (18–24 months), root resorption, and formation of fenestrations and dehiscence. Periodontally accelerated osteogenic orthodontics (PAOO) is a surgical technique resulting in increased alveolar bone width, shorter treatment time, increase posttreatment stability, and decrease amount of apical root resorption.Aim:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…However, there were some postoperative complications with surgical bur such as root resorption. [ 20 ] Hajji reported similar outcomes in their study. [ 21 ] Chung et al .…”
Section: Discussionsupporting
confidence: 58%
“…However, there were some postoperative complications with surgical bur such as root resorption. [ 20 ] Hajji reported similar outcomes in their study. [ 21 ] Chung et al .…”
Section: Discussionsupporting
confidence: 58%
“…The case was managed and the patient was monitored until she returned to her normal condition. Later, she was contacted on the same day and confirmed that she was in good health without any symptoms [ 54 ] The monthly repetition of MOPs caused fear since some patients were afraid and asked to not undergo the perforations [ 41 ] % 2.2% Total n 8 % 8.8% Other harms Numbness n 1 Corticotomy [ 46 ] One patient had numbness in the corner of the upper lip, which lasted for approximately a month and then disappeared after being given nerve repair medication [ 46 ] % 1.1% Hematoma n 2 PAOO [ 53 ], Flapless corticotomy using bur [ 55 ] 3 out of 20 patients in the PAOO with piezocision group experienced hematoma of the chin [ 53 ] One patient developed a significant hematoma in the lower lip while applying flapless corticotomy using bur [ 55 ] % 2.2% Total n 3 % of total 3.3% Total …”
Section: Resultsmentioning
confidence: 99%
“…Harms that were related to patient-centered outcomes were mentioned in eight papers (8.8%, Table 5 ). These complications had several forms such as postoperative pain [ 41 , 51 , 52 ], discomfort [ 43 , 50 ], swelling (which was reported by the patients themselves and not those observed by the researchers) [ 44 , 50 53 ], and in one paper, dizziness and hypotension accompanied by fear of undergoing the surgical intervention [ 41 ]. Also, there was a fear of repeating the surgical intervention [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Rajasekaran and Krishna Nayak,[36] mild pain was reported that persisted for 3 days. Thind et al .,[37] observed negligible root resorption when PAOO was performed with a piezosurgical unit and surgical bur.…”
Section: Discussionmentioning
confidence: 99%